Система контролю зношуванням висікального інструмента - Гуліда, Едуард; Паламар, Олег; Сторощук, Володимир (КІНПАТРІ ЛТД, 2013)
The proposed control system wear cutting tools for the production of cardboard packaging products manufacturing.
Control system wear of cutting tools